2020
DOI: 10.3390/en13071684
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Boundary Conditions Considering Influence Factors of the Room Equipped with a Ceiling Radiant Cooling Panel

Abstract: The objective of this study is to establish boundary conditions to evaluate the cooling capacity of the Cooling Radiant Ceiling Panel (CRCP) considering the environment of a room equipped with the CRCP. The current study investigated the boundary conditions and derivation techniques from previous studies. Based on the results of the analysis, a heat transfer model was derived for a room fitted with CRCP. In addition, the heat transfer model was used to derive the factors affecting the cooling capacity of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Internal heat gains increase the building's interior temperature and may considerably contribute to the building's thermal balance, especially in well thermally insulated objects [5,8]. The importance of IHG for thermal and energy performance of buildings were also addressed in [9][10][11][12]. In the subject literature, the terms "heat gains" and "heat loads" are often used interchangeably [7].…”
Section: Internal Heat Gainsmentioning
confidence: 99%
“…Internal heat gains increase the building's interior temperature and may considerably contribute to the building's thermal balance, especially in well thermally insulated objects [5,8]. The importance of IHG for thermal and energy performance of buildings were also addressed in [9][10][11][12]. In the subject literature, the terms "heat gains" and "heat loads" are often used interchangeably [7].…”
Section: Internal Heat Gainsmentioning
confidence: 99%
“…It was found that condensation was prevented because the minimum surface temperature was always higher than dew-point temperature. In addition, the use of openings or air circulators reduced the difference (∆θ) between the mean chilled water temperature and room air temperature, which is formulated as Equation (3).…”
Section: Cooling Capacity Analysismentioning
confidence: 99%
“…As closed-type CRCP systems separate a plenum and an occupied space, it is difficult to utilize cooled plenum air to cool the occupied space. This separation does not lead to problems for the top-insulated panels that minimize the heat transfer at the upper surface of CRCPs [3,4]. However, metal ceiling panels without top insulation, which are commonly installed in office buildings, can absorb heat from the plenum space [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As diverse lifestyles emerge in modern society, which was once dominated by mass consumption, people's interests have shifted from quantity to quality, resulting in a heightened demand for improved quality of life. This includes a higher level of thermal comfort within buildings [1]. Consequently, radiant heating systems are being adopted as an alternative to address the discomfort caused by air currents discharged from convective heating systems during the winter period.…”
Section: Introduction 1background and Purposementioning
confidence: 99%